Intikhab-e-Kalam : Meeraji - Meeraji; Edited and introduced by Asif Farrukhi (Karachi Oxford University Press, 2014)
This is a selection of poems by Meeraji, who initially struck litterateurs as odd and whose poems contained ambiguity of a level not found earlier in Urdu poetry. Shortly after his death, Meeraji came to be regarded as a leading modern Urdu poet and he became a veritable cult figure. Never before had ambiguity and lyricism come together as they did in the poems of Meeraji. His sensibility was discovered to be rare but genuine and his oeuvre has been hailed as a classic.
Keywords: Urdu Literature - Poetry -- Poetry in Urdu -- Urdu Literature - Poetry -- Intikhab e Kalam : Meeraji